THE IMPORTANCE OF CAREER GUIDANCE AND COUNSELING SERVICES ACCORDING TO THE BENEFICIARIES - ROXANA PLEŞA; ROBERT PRODANCIUC; IRINEL STEGAR; CRISTIAN ILIONI (Annals of the University of Petrosani: Economics)
The quality of an education system is reflected not only in the educational performance of the educational actors, but also by the measure to which it ensures an adequate professional integration. Today's student, tomorrow's graduate needs information as accurate as possible regarding the labor market, this fact can’t be accomplished only with their own resources it also requires career guidance services. In universities counseling is in a debut phase and tries to consolidate its status by various adequate informing and promoting actions focused on the beneficiaries of this type of counseling. The motivation for choosing this research subject resides in observing the growing number of people that become aware of the need for and the utility of this type of counseling.